2014
DOI: 10.1089/met.2013.0127
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Prevalence of Metabolic Syndrome in Adolescents According to Different Criteria Used for Diagnosis: Which Definition Should Be Chosen for This Age Group?

Abstract: Metabolic syndrome and its components were conditions present in the adolescents of this study. In this population, with a high prevalence of dyslipidemia and a lower prevalence of abdominal obesity and hyperglycemia, the recommendation to diagnose metabolic syndrome would be that used by Ford et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 40 publications
4
56
0
17
Order By: Relevance
“…Various publications have noticed prevalence numbers ranging from 0.2% to 38.9% (22). In a systematic review of 85 studies in children, the median prevalence of metabolic syndrome in whole populations was 3.3% (range 0-19.2%), in overweight children was 11.9% (range 2.8-29.3%), and in obese populations was 29.2% (range 10-66%).…”
Section: Epidemiologymentioning
confidence: 99%
“…Various publications have noticed prevalence numbers ranging from 0.2% to 38.9% (22). In a systematic review of 85 studies in children, the median prevalence of metabolic syndrome in whole populations was 3.3% (range 0-19.2%), in overweight children was 11.9% (range 2.8-29.3%), and in obese populations was 29.2% (range 10-66%).…”
Section: Epidemiologymentioning
confidence: 99%
“…This large range can mainly be attributed to the inconsistent definition of the term metabolic [13]. According to Agudelo et al [14], the current cutoff points are highlighted in table 2. Depending on classification, the occurrence varies between 0.9, 3.8, 4.1, 10.5, and 11.4% corresponding to International Diabetes Federation [19], Cook et al [15], Ford et al [17], Agudelo et al [18], and de Ferranti et al [16], respectively.…”
Section: Definition and Prevalence Of The Metabolic Syndrome In Childmentioning
confidence: 99%
“…Furthermore, insulin resistance causes the metabolic alterations that finally results in metabolic syndrome (MetS) [23][24][25][26][27] and prevalence of MetS is directly proportional to the obesity [28][29][30]. A recent study in Medellin on 851 adolescents aged between 10 to 18 years old revealed rates of 25%, 4.1%, and 4.9% for overweight, MetS, and insulin resistance respectively [26]. The biological findings associated with this disease suggest that the β-pancreatic cells of these adolescents are forced to produce more insulin to maintain normoglycaemia, which predisposes them to hyperglycaemia and Diabetes Mellitus type 2 [27,31,32].…”
Section: Discussionmentioning
confidence: 99%